Measurement errors in statistical process monitoring: A literature review. (January 2017) - Maleki, Mohammad Reza; Amiri, Amirhossein; Castagliola, Philippe
Highlights: An overview on the effect of measurement errors on different areas of SPM. Providing a comprehensive classification of articles in this area. Presenting an analytical overview on the researches in this area. Introducing research gaps in this area to motivate future studies. Abstract: In most industrial applications, the measures performed on inspected units are often strongly contaminated by either the inspector or the measuring device leading to measurement errors. It is recognized that the measurement errors affect the performance of control charts in various statistical process monitoring applications. In this paper, we present a conceptual classification scheme based on content analysis method to analyze and categorize the researches which have explored the effect of measurement errors on different aspects of statistical process monitoring (SPM). Moreover, based on 60 relevant papers in this field, the research gaps are mentioned and some directions to motivate the future studies are provided.